2022
DOI: 10.1590/0103-11042022e409
|View full text |Cite
|
Sign up to set email alerts
|

Gestão participativa na Atenção Primária à Saúde: ensaio sobre experiência em território urbano vulnerável

Abstract: RESUMO A gestão participativa, embora instituída nas normativas de constituição do Sistema Único de Saúde, ainda encontra desafios para efetivação em âmbito local, especialmente em territórios urbanos marcados por violência e pobreza. O ensaio objetivou apresentar e discutir aspectos de uma experiência de gestão participativa em um território vulnerável, mediada pela Atenção Primária à Saúde. Essa experiência de cogestão da saúde foi desenvolvida entre 2009 e 2013 em Manguinhos, no município do Rio de Janeiro.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 14 publications
0
0
0
Order By: Relevance
“…The percentage of COVID-19 among women found in our study is likely related to the fact that women seek more health services than men 36 . In addition, we observed that the population registered in the Manguinhos Family Health Strategy has a slight female predominance (54%), which may also have contributed to explaining this small difference in the proportion of cases found according to sex 37 .…”
Section: Discussion Main Finding Of This Studymentioning
confidence: 77%
“…The percentage of COVID-19 among women found in our study is likely related to the fact that women seek more health services than men 36 . In addition, we observed that the population registered in the Manguinhos Family Health Strategy has a slight female predominance (54%), which may also have contributed to explaining this small difference in the proportion of cases found according to sex 37 .…”
Section: Discussion Main Finding Of This Studymentioning
confidence: 77%